Chromosomal microarray analysis is superior in identifying cryptic aberrations in patients with acute lymphoblastic leukemia at diagnosis/relapse as a single assay. (21st May 2019) - Chen, Chuanfei; Heng, Evelyn Yee Hsieh; Lim, Alvin Soon Tiong; Lau, Lai Ching; Lim, Tse Hui; Wong, Gee Chuan; Tien, Sim Leng
Abstract: Introduction: Conventional cytogenetics (CC) is important in diagnosis, therapy, monitoring of post‐transplant bone marrow, and prognosis assessment of acute lymphoblastic leukemia (ALL). However, due to the nature of ALL, CC often encounters difficulties of complex karyotype, poor chromosome morphology, low mitotic index, or normal cells dividing only. In contrast, chromosomal microarray analysis (CMA) showed a specificity >99% and a sensitivity of 100% in chronic lymphocytic leukemia (CLL) patients. Here, we report our experience with CMA on adult ALL patients. Methods: Thirty‐three bone marrow/blood samples from ALL patients (aged 18‐79 years, median 44) at diagnosis/relapse, analyzed by CC and/or fluorescence in situ hybridization (FISH), were recruited. Chromosomal microarray analysis results were compared with CC. Fluorescence in situ hybridization analysis, if available, was applied when there was a discrepancy. Results: Copy‐neutral loss‐of‐heterozygosity (CN‐LOH) was found in 8 cases (24.2%). Only CN‐LOH at 9p was recurrent (3 cases, 9.1%). Copy number alterations (CNAs) were detected in 6 of 9 cases (66.7%) with normal karyotypes, in 3 of 5 cases (60.0%) with sole "balanced" translocations, and in 18 of 19 cases (94.7%) with complex karyotypes. Common CNAs involved CDKN2A/2B (30.3%), IKZF1 (27.3%), PAX5 (9.1%), RB1 (9.1%), BTG1 (6.7%), and ETV6 (6.7%), which regulate cell cycle, B lymphopoiesis, or act as tumor suppressors in ALL. Copy number alteration detection rate by CMA was 81.8% (27 of 33 cases) as compared to 57.6% (19 of 33 cases) by CC. Conclusion: Incorporation of CMA as a routine clinical test at the time of diagnosis/relapse, in conjunction with CC and/or FISH, is highly recommended.